2017
DOI: 10.1097/bsd.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Complications, Readmissions, and Revisions for Spine Procedures Performed by Orthopedic Surgeons Versus Neurosurgeons

Abstract: Level 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…It has been reported that there was a statistically significant difference between neurosurgeons and orthopedic surgeons in the type of discectomy, the value of intervention after complete spinal cord injury, and the use of orthoses after fusion surgery 13) . However, other studies have demonstrated that surgeons with either training background can achieve similar results and have similar competence when treating common spinal pathologies 22,24,38) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there was a statistically significant difference between neurosurgeons and orthopedic surgeons in the type of discectomy, the value of intervention after complete spinal cord injury, and the use of orthoses after fusion surgery 13) . However, other studies have demonstrated that surgeons with either training background can achieve similar results and have similar competence when treating common spinal pathologies 22,24,38) .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3]13,19,21,23,26,29 Variations by spine surgeon specialty have been studied, but no significant differences were noted between orthopedic and neurological surgeons in spine surgery. 22,24,25 Our findings suggest that patient characteristics may be important factors influencing readmission rates. Programs that target physicians to reduce readmission rates may have limited effectiveness.…”
Section: Discussionmentioning
confidence: 68%
“…Even with use of the “gold standard” of autograft, surgeons commonly deal with revision surgery rates of ±10%–20%. 23 – 26 Considering this, it is important that the selection of graft materials is based on preclinical evidence obtained in studies of high methodological quality, using clinically relevant animal models and multiple evaluation techniques. A large number of bone grafts are commercially available for clinical use, which makes selection of the most appropriate challenging for the surgeon community.…”
Section: Discussionmentioning
confidence: 99%